Pelatihan Urban Farming Hidroponik di Kecamatan Tembok Dukuh Surabaya - Theresa Widya Artika; Efendi Surahman (UNITY: Journal of Community Service, 2025)
This community service activity aims to enhance the knowledge and skills of local residents, particularly women from the Family Welfare Movement (PKK), in utilizing limited land through hydroponic-based urban farming methods. Tembok Dukuh District, a densely populated area in Surabaya, faces limited green space and a high dependency on external food supplies. Through this program, participants were introduced to the concept of hydroponics, trained in constructing simple installations, and taught techniques for planting and maintaining vegetables. The implementation method included socialization, hands-on demonstrations, and mentoring sessions over a three-week period. The results showed a significant improvement in participants' understanding of hydroponic systems and their ability to apply these techniques in their home environments. This initiative is expected to serve as a sustainable solution for strengthening household food security and fostering creative economic opportunities in urban areas.